Enhancing resistance to low-velocity impact of electrospun-manufactured interlayer-strengthened CFRP by using infrared thermography; NDT & E International; Vol. 144 - Zhu Pengfei; Hai Zhang; Stefano S. Sfarra; Usamentiaga R. Ruben; Sarasini F. Fabrizio; Vavilov V. P. Vladimir Platonovich; Ibarra-Castanedo C. Clemente; Maldague X. Xavier (2024, 2024)
Title screen